Results of introduction of wood plants in the SE EF Novokakhovs’ke(Nikitsky Botanical Garden–National Scientific Center) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
The outcomes of introductionand overwintering in winter 2005-2006are adduced of 35species wood plants in State Enterprise Experimental Farm Novokakhovskoe of Nikita Botanical Garden National Scientific Center.
Keywords: introduction, damage, temperature.